Papel do fator de troca de nucleotídeos guanina RasGEF1b na resposta imune ao protozoário parasito Trypanosoma cruzi - Heliana de Barros Fernandes (2018)
Trypanosoma cruzi, the causative agent of Chagas disease, activates receptors present on cells of innate immunity, such as Toll-like receptors. Intracellular signaling triggered in cells such as macrophages and cardiomyocytes leads to the activation of genes and consequent production of critical inflammatory mediators during infection. In addition to these secreted factors, such cytokines and chemokines, intracellular signaling proteins may play a role during the host control of T. cruzi infection. RasGEF1b is a guanine nucleotide exchange factor whose expression is induced in macrophages treated with tGPI-mucin and in vivo in tissues as the heart and liver of mice infected with T. cruzi. However, the role of RasGEF1b during the infection by this parasite still unknown. In this work, complete knockout mice (RasGEF1b-KO) or with conditional deletion of Rasgef1b in hematopoietic cells [RasGEF1b(Hc)-KO] were used to investigate the role of this molecule in the innate immune response to T. cruzi. In vitro analyzes were performed on bone marrow derived macrophages from wild type and and knockout mice. In infected cells no differences were observed in the events of internalization, intracellular multiplication and parasite release. In an in vivo infection model, RasGEF1b deficiency did not affect the control of parasites in the blood and survival of the animals. However, in RasGEF1b(Hc)-KO mice the serum concentration of Ifn-γ and Il-6 was significantly higher at 15th day post-infection. Interestingly, the production of Ifn-γ by splenocytes or liver non-parenchymal cells was also elevated in the RasGEF1b (Hc)-KO mice. Histopathological analyzes revealed that inflammation in the liver and heart of RasGEF1b(Hc)-KO mice is higher when compared to WT. However, this enhanced inflammatory infiltrate did not implicate an improvement in the control of tissue parasite load. Despite the increased concentration of Ifn-γ, no hepatic damage was detected in infected RasGEF1b(Hc)-KO mice. Taken together, these results revealed that RasGEF1b is not essential for systemic parasite control during the acute phase of T. cruzi infection, but may act as a negative regulator of Ifn-γ and Il-6 production in a cell-specific manner. Considering that myocarditis is a major cause of morbidity among chagasic patients, we generated conditional knockout mice from RasGEF1b on cardiomyocytes [RasGEF1b(Cm)-KO]. We have shown that RasGEF1b is the most abundant member of the RasGEF1 family in the heart and in cardiomyocytes. During the acute phase of T. cruzi infection, RasGEF1b(Cm)-KO mice survive but show a delay in the peak of parasitemia. Our data suggest an in vivo role of RasGEF1b in cells of hematopoietic origin and in cardiomyocytes during the acute phase of Chagas disease.